(untitled) - Richardson, Alan (Cambridge,New York, 2001)
In this provocative and original study, Alan Richardson examines an entire range of intellectual, cultural, and ideological points of contact between British Romantic literary writing and the pioneering brain science of the time. Poets such as Wordsworth, Coleridge, and Keats, and novelists such as Jane Austen and Mary Shelley, are shown to have shared a surprising extent of common ground with pioneering brain scientists including Erasmus Darwin and F. J. Gall. It demonstrates the value for literary and cultural history of learning from recent work in neuroscience and cognitive science
Keywords: English literature,Literature and science,Brain,Mind and body in literature,Văn học Anh,Tâm hồn và thể xác trong văn học; History and criticism,History,Research,History,Lịch sử và phê bình; 19th century,19th century,19th century,Thế kỷ 19; Great Britain,Great Britain